TINJAUAN HUKUM TERHADAP PERAN DAN TANGGUNG JAWAB PERUSAHAAN JASA MAKLON DALAM PRODUKSI DAN DISTRIBUSI PRODUK KOSMETIK - Wahyuni Safitri (Law Department, University of Widya Gama Mahakam Samarinda, 2025)
This study aims to analyze and determine the role and influence of maklon service companies in the production and distribution process of cosmetic products from a corporate law perspective, and to analyze and determine the form of legal guarantees and responsibilities of maklon service companies to consumers in cases of illegal product circulation. The method used in this study is a qualitative method, with a normative legal approach. The results of the study indicate that maklon service companies have a strategic role in the cosmetics industry by providing efficient production and distribution services. The role of maklon service companies in cosmetic production is to provide cost and time efficiency for cosmetic business actors, maintain and improve product quality, and provide innovation to cosmetic business actors' products. While the role of maklon service companies in the distribution of cosmetic products is to ensure compliance with regulations and permits, provide products on a large scale, and provide data and formulation protection. Maklon service companies have a great responsibility in ensuring that the cosmetic products they produce comply with applicable regulations. Forms of legal guarantees to consumers include product safety guarantees, information disclosure guarantees, and compensation and settlement guarantees. While maklon service companies have a great responsibility in preventing the circulation of illegal products. The form of legal responsibility of the maklon service company towards consumers in cases of illegal product distribution is responsibility for breach of contract, administrative responsibility (sanctions from BPOM and the Government), civil responsibility (compensation to consumers), and criminal responsibility (imprisonment and fines).